Synthesis of Nico-bimetallic nitride/graphene oxide/Ti3C2 MXene hybrid electrode for supercapacitors - Samson, Elendu Ekwueme; Supeni, Eris Elianddy; Mohd Arffin, Mohd Khairol Anuar; Shafie, Suhadi; Ishaq, Muhammad (ModTech Publishing House, 2025)
It is becoming more widely acknowledged that energy storage technologies are essential to achieving sustainable development objectives. Effective energy storage technologies are essential for improving grid stability, permitting greater integration of renewable energy, and lowering dependency on fossil fuels as international efforts to slow down climate change and switch to renewable energy sources increase. By addressing intermittency issues and facilitating the efficient utilization of renewable resources such as solar and wind power, advancements in energy storage contribute significantly to building resilient, low-carbon energy systems essential for sustainable development. The goal of this work is to improve the specific capacitance, rate capability, and cycling stability of supercapacitors by synthesizing and characterizing a novel hybrid electrode material made of reduced graphene oxide, bimetallic NiCo-nitride, and Ti3C2 MXene. The two-step synthesis technique created a bimetallic NiCo-nitride/reduced graphene oxide/Ti3C2 MXene hybrid from NiCo-layered double hydroxide (LTHs) on a flexible nickel foam substrate (named NCN@rGO/Ti3C2/NF). First, NC-LDH@rGO/Ti3C2/NF nanosheets were grown hydrothermally in situ on the nickel foam surface. This was followed by thermal annealing in an NH3 environment at temperatures between 300 and 500°C. Based on electrochemical measurements, the NCN@rGO/Ti3C2/NF hybrid electrode annealed at 500°C (NCN@rGO/Ti3C2/NF-500) showed exceptional cycling stability of 93.8% after 3500 cycles and excellent rate capability of 92.2% at 20 Ag-1. Its specific capacitance reached 1032.71 Fg-1 at 0.5 Ag-1.